Risk Factors Associated With Increased Mortality From Intussusception in African Infants. Issue 1 (January 2020) - Pindyck, Talia; Parashar, Umesh; Mwenda, Jason M.; Tadesse, Amezene; Armah, George; Omore, Richard; Ngwira, Bagrey; Jani, Bhavin; Mpabalwani, Evans M.; Mbuwayesango, Bothwell; Tate, Jacqueline
ABSTRACT: Objectives: Morbidity and mortality from intussusception, the leading cause of bowel obstruction in infants, is higher in Africa than in other regions of the world, but the reasons have not been well examined. We sought to identify risk and protective factors associated with death or intestinal resection following intussusception. Methods: Infants with intussusception from 7 sub-Saharan African countries (Ethiopia, Ghana, Kenya, Malawi, Tanzania, Zambia, and Zimbabwe) were enrolled through active, hospital-based surveillance from February 2012 to December 2016. We examined demographic, clinical, and socioeconomic factors associated with death or intestinal resection following intussusception, using multivariable logistic regression. Results: A total of 1017 infants <1 year of age with intussusception were enrolled. Overall, 13% of children (133/1017) died during the hospitalization, and 48% (467/966) required intestinal resection. In multivariable analyses, female sex [odds ratio (OR) 1.8, 95% confidence interval (CI) 1.2–3.3], longer duration of symptoms before presentation (OR 1.1; 95% CI 1.0–1.2), and undergoing intestinal resection (OR 3.4; 95% CI 1.9–6.1) were associated with death after intussusception. Diagnosis by ultrasound or enema (OR 0.4; 95% CI 0.3–0.7), and employment of a household member (OR 0.7; 95% CI 0.4–1.0) were protective against intestinal resection. Conclusions: Delays in hospital presentation and female sex were significantly associated with death, whereas higher socioeconomic status and availability of radiologic diagnosis reduced likelihood of undergoing resection. Efforts should be intensified to improve the awareness, diagnosis, and management of intussusception in sub-Saharan African countries to reduce morbidity and mortality from intussusception in these resource-limited settings. Abstract : Supplemental Digital Content is available in the text